Resistance of Aedes aegypti (L.) (Diptera: Culicidae) to Temephos in Brazil: A Revision and New Data for Minas Gerais State - Horta, Marco Aurélio P.; Castro, Francimar I.; Rosa, Cassiano S.; Daniel, Michel C.; Melo, Alan L. (BioAssay, 2011)
Dengue fever affects thousands of people in tropical regions of the world. Governmental health service in Brazil has used organophosphates like temephos against Aedes aegypti larvae since 1967 but today in several regions of Brazil authors have reported an increase of tolerance of Ae. aegypti to temephos. Since 1986 when dengue fever was introduced to Brazil, the disease has been detected every year. In Minas Gerais State, the major epidemics occurred in 1998 followed by a brand new epidemic peak at the beginning of 2002. Aiming to verify the susceptibility of Ae. aegypti population to temephos in the municipality of Coronel Fabriciano, Minas Gerais State, temephos resistance bioassays with diagnostic dose (0.012 mg/L) were performed with F1 larvae of natural populations of Ae. aegypti collected with ovitraps. The bioassays 1, 2, 3 and 4 presented mortality rates for Rockefeller population of 97%, 100%, 100% and 99% respectively. Mortality rates for natural population were 5.12%, 3.37%, 0% and 2.66% for bioassays. The average mortality was 2.78% for natural population and 99% for Rockefeller mosquitoes. Results show that the exposure of Ae. aegypti larvae to different concentrations of temephos revealed resistance in several localities examined. Comparisons with the results obtained by authors for other regions in Brazil show that mortality obtained vary from 0.0 to 100% with mean of 39.29% ± 30.13. Results presented in this paper serve as parameter to possible changes in Brasil’s Dengue Control Program aiming the insecticide resistance management.